IMMUNOSUPPRESSIVE THERAPY AFTER LIVER TRANSPLANTATION AND PREVENTION OF REJECTION SYNDROME - Shavkat Amanov Sherzod o’g’li; Muxammadiyeva Sevinch Baxromovna; Qurbonboyev Sardor Sunnatilla oʻgʻli (Modern American Journals, 2026)
Background: Liver transplantation (LT) is a life-saving procedure for patients with end-stage liver disease and hepatocellular carcinoma. Long-term survival and graft function depend largely on effective immunosuppressive therapy. However, clinical practice varies widely across Western, Asian, and resource-limited countries due to differences in epidemiology, donor sources, healthcare infrastructure, and drug availability.
Keywords: Liver transplantation (LT), Asian Liver Transplant Network (ALTN), Living donor liver transplantation (LDLT), Deceased donor liver transplantation (DDLT), Hepatocellular carcinoma (HCC), Hepatitis B virus (HBV), Hepatitis C virus (HCV), Immunosuppression